The Literary Tale in Pre-Lslamic Era: A Study in Concealed Manners - NAAIL ABDUL HUSSEIN ABDUL SAYED, Dr. (lark, 2023)
This study investigates samples of tales that accompany poetry in the pre-Islamic literature. It aims at studying them in the light of cultural studies in orderto know the reasons for their duration, recurrence, constancy and transmission. Itexamines these tales as far as their credibility, plagiarism or fabrication. It alsodiscusses the opinions about them and the different aspects of each tale inaddition to the differences between these aspects. It shows the contradictionsand conformities between them. In order to succeed in this investigation, thestudy depends on the history of literature as an accompanying base. It brings tolight the literary, historical and logical paradoxes of these tales, compares themto accompanying poetry and show how the narrated text corresponds to thepoetic text. It takes into account the social, economic, political and inclinationalconditions of that time in general and of the authors of these tales in particular.
Keywords: Key words: eminency of the poet, plagiarism, balancing, poetics, paradox.